2016
DOI: 10.1155/2016/3242698
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Antiproliferative Activity Assay of Clove Mistletoe (Dendrophthoe pentandra(L.) Miq.) Leaves Extracts

Abstract: Clove mistletoe (Dendrophthoe pentandra (L.) Miq.) is a semiparasitic plant that belongs to Loranthaceae family. Clove mistletoe was traditionally used for cancer treatment in Indonesia. In the present study, we examined cytotoxicity of clove mistletoe leaves extracts against brine shrimps and conducted their antiproliferative activity on K562 (human chronic myelogenous leukemia) and MCM-B2 (canine benign mixed mammary) cancer cell lines in vitro. The tested samples were water extract, ethanol extract, ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 20 publications
1
39
1
4
Order By: Relevance
“…These findings suggest that the extract of this plant has the important role in inhibiting intestinal inflammation [1]. Extracts of D. pentandra have also been reported to effectively inhibit inflammation, proliferation and induce p53 expression on mice models of colitis-associated colon cancer [28].Analysis of cytotoxicity revealed that the extracts of D. pentandra had cytotoxic effects on K562 and MCM-B2 cell lines thus suggestive of a potential anticancer activity of this plant [29]. Methanolic extracts of D. pentandra leaves have been also found to exert potent anti-proliferative effects on BCR/ABL-Positive and Imatinib Resistant Leukemia Cell lines [30].…”
Section: Discussionmentioning
confidence: 89%
“…These findings suggest that the extract of this plant has the important role in inhibiting intestinal inflammation [1]. Extracts of D. pentandra have also been reported to effectively inhibit inflammation, proliferation and induce p53 expression on mice models of colitis-associated colon cancer [28].Analysis of cytotoxicity revealed that the extracts of D. pentandra had cytotoxic effects on K562 and MCM-B2 cell lines thus suggestive of a potential anticancer activity of this plant [29]. Methanolic extracts of D. pentandra leaves have been also found to exert potent anti-proliferative effects on BCR/ABL-Positive and Imatinib Resistant Leukemia Cell lines [30].…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the highest total phenolic content and iron‐chelating ability among the three different plant parts extracts (leaf, stem, and flower) of S. ferruginea were also found to be in the stem. A number of studies on the other mistletoe genera of Loranthaceae had indicated a strong host‐dependency of many tested bioactivities including anti‐cancer, antiviral, antioxidant, anti‐diabetes, decreasing hypertension, and others …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the use of this extract may have/exert negative/adverse effect during painful crisis in sickle cell anemia, similar to caffeine (Wang et al 2009). In contrast, the effect of this plant on membrane of blood cells may be employed to increase the efficacy of antitumor therapy, accordingly to previous report (Elsyana et al 2016, Saghir et al 2016, Tabrizi et al 2016. The potentiation in NPSH and in the hemolysis in erythrocytes treated with plant extracts and t-BHP deserves, doubtless, further research to investigate the involved mechanism(s).…”
mentioning
confidence: 80%